Trade and Power, Money and War: Rethinking Masculinity in Michael Ondaatje's The English Patient - Ellis, Susan (Studies in Canadian Literature)

(untitled) (None, 1996)
Michael Ondaatje's The English Patient attempts to depict the possibility of a truly differentiated self defined through particular relationships to others, rather than in isolation from them. Ondaatje links issues of ownership with the power of naming. Through the act of naming, creation of a sense of self can be a political act of empowerment. Ondaatje creates a sense of power by filling the novel with stories of the new man replacing the old.